Regional Economic Outlook, October 2010, Europe, Building Confidence. (Regional Economic Outlook, 2010)
The recovery in Europe continues, supported by strong policy action to contain sovereign debt problems in the euro area. In advanced Europe, lingering uncertainties and market pressures make for moderate and unequal growth, creating challenges for macroeconomic and financial sector policies. The REO also sheds light on the governance issues revealed by the crisis, arguing that better policy frameworks, in particular at the euro area level, promise a stronger Europe. For the first time, the REO devotes a separate chapter to the outlook for emerging Europe, where, after a deep recession, an export-led recovery is under way. However, the rebound is uneven across the region, and policymakers face the difficult challenge of dealing with the legacies of the crisis, while not hurting the recovery. Beyond the short term, the REO argues that the region will need to find new growth engines, as the capital inflows-driven and credit-fueled domestic demand boom needs to give way to more balanced growth. Indeed, the REO emphasizes that active fiscal policy and coordinated prudential measures are key to avoiding a repeat of the boom-bust cycle the region has just endured.